Determinants of profitability of local takaful companies in Malaysia / Anis Amalina Ismail - Ismail, Anis Amalina (2013)
Takaful industry plays an important role in prevailing needs of the Muslim public. Takaful system has shown better development and now is widely accepted by Muslims as well as non-Muslims in Malaysia. The objective of this study is to examine the determinants of local Takaful companies in Malaysia. Therefore, the aim of this paper is to measure the profitability of Takaful industry and identify the factors affecting the profitability. The sample selected are from eight Takaful companies annual report in Malaysia from year 2008 until 201 1 using the method employed Generalized Least Square (GLS) panel data analysis. The dependant variables of this study are profitability of Takaful industry in Malaysia. The independent variables that affect Takaful industry profitability are firm size, liquidity, inflation, and return on equity (RO . The expected findings are positive relationship between liquidity and return on equity (ROE) towards its profitability and find a negative insignificant relationship between firm size and inflation towards profitability. Increased exposure to credit risk is normally associated with decreased firm profitability; hence, a negative relationship is expected between ROA and CR. This study found negative relationship between inflation and profitability.